Hepatitis C Virus Antibodies and Vitiligo Disease - Z Jadali; MB Eslami; MH Sanati; P Mansouri; M Mahmoudi; N Maghsoudi; F Esfahanian (Tehran University of Medical Sciences, 2005)
Vitiligo is a common skin disorder, characterized by depigmented patches due to selective destruction of melanocytes. The etiology of this disease is unknown. A number of hypotheses including viral theory have been proposed to explain the etiology. To determine the prevalence of antibody to hepatitis C virus infection in vitiligo patients, the present study was performed. Third generation ELISA test was used for detection of antibodies to HCV in human sera. All normal controls were anti-HCV negative whereas only one patient was positive for anti-HCV and there was no significant difference in the prevalence of anti-HCV between patients and controls. These results indicate that hepatitis C virus has not a direct causal role in the pathogenesis of vitiligo, however, this does not rul out a "hit and run" virus induced disease.